Impact of Stroke Length Variation on Speed Efficiency in an Authomatic Tofu Extract Filtering Machine - Saputro, Danang Dwi; Pangestu, Wahyu Dwi (Universitas Negeri Semarang, 2022)
In the tofu industry, especially at the home-scale